Evaluation of the post-coital anti-fertility activity of Michelia champaca linn. aerial extract in female Wistar rat - Devi, Seema; Mohan, Chander (Journal of Applied Pharmaceutical Research, 2024)
Background: The plant M. champaca L., commonly known as Champa, has traditionally been utilized for its medicinal properties, particularly in women's health, for managing sterility and birth control. Previous literature primarily focuses on the anti-fertility activity of leaf extracts, while limited research has explored the potential of other aerial parts, such as the bark and flowers. Therefore, this study aims to investigate the female anti-fertility actions of various aerial parts (including leaves, branches, bark, and flowers) of the M. champaca plant, expanding our understanding beyond the previously studied leaf extracts. Material and Method: The petroleum ether (PEAEMC), ethyl alcohol (EAEMC), and chloroform water (AAEMC) extracts of aerial parts of M. champaca at doses of 100 mg/kg and 200 mg/kg were administered to female Wistar rats by using an experimental model, i.e., anti-implantation and estrogenic/Anti-estrogenic activity. Result: All three extracts showed significant anti-implantation activity (p<0.01). Among all, only EAEMC Showed activity corresponding to the standard. EAEME caused an increase in the vaginal opening size and increased height and width of the endometrium in immature ovariectomized female rats; it showed an estrogen-like action when given alone, however when given along with Ethinylestradiol, it showed anti-estrogenic action. Conclusion: It was observed that EAEMC (the Ethyl alcohol extract of M. champaca) showed dose dependent anti-fertility activity. The chemical constituents like steroids, alkaloids, and flavonoids identified from the photochemical screening may be responsible for the anti-fertility activity of the aerial parts of M. champaca L.